Insulin Resistance Impairs Circulating Angiogenic Progenitor Cell Function and Delays Endothelial Regeneration - Kahn, Matthew B. (American Diabetes Association, 2011)
OBJECTIVE: Circulating angiogenic progenitor cells (APCs) participate in endothelial repair after arterial injury. Type 2 diabetes is associated with fewer circulating APCs, APC dysfunction, and impaired endothelial repair. We set out to determine whether insulin resistance adversely affects APCs and endothelial regeneration. RESEARCH DESIGN AND METHODS: We quantified APCs and assessed APC mobilization and function in mice hemizygous for knockout of the insulin receptor (IRKO) and wild-type (WT) littermate controls. Endothelial regeneration after femoral artery wire injury was also quantified after APC transfusion. RESULTS: IRKO mice, although glucose tolerant, had fewer circulating Sca-1(+)/Flk-1(+) APCs than WT mice. Culture of mononuclear cells demonstrated that IRKO mice had fewer APCs in peripheral blood, but not in bone marrow or spleen, suggestive of a mobilization defect. Defective vascular endothelial growth factor–stimulated APC mobilization was confirmed in IRKO mice, consistent with reduced endothelial nitric oxide synthase (eNOS) expression in bone marrow and impaired vascular eNOS activity. Paracrine angiogenic activity of APCs from IRKO mice was impaired compared with those from WT animals. Endothelial regeneration of the femoral artery after denuding wire injury was delayed in IRKO mice compared with WT. Transfusion of mononuclear cells from WT mice normalized the impaired endothelial regeneration in IRKO mice. Transfusion of c-kit(+) bone marrow cells from WT mice also restored endothelial regeneration in IRKO mice. However, transfusion of c-kit(+) cells from IRKO mice was less effective at improving endothelial repair. CONCLUSIONS: Insulin resistance impairs APC function and delays endothelial regeneration after arterial injury. These findings support the hypothesis that insulin resistance per se is sufficient to jeopardize endogenous vascular repair. Defective endothelial repair may be normalized by transfusion of APCs from insulin-sensitive animals but not from insulin-resistant animals.